Integration of Islamic Education in Indonesian Language Learning as an Effort to Shape the Character of Students at MAN 2 Majalengka - Endah Meilani Sari (TA'DIB: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the integration of Islamic Education into Indonesian Language learning as a strategic effort to build the Islamic character of students at MAN 2 Majalengka, West Java. Employing a sequential explanatory mixed methods design, the study collected quantitative data from 80 students using a Likert-scale character assessment instrument measuring five dimensions religiosity, integrity, cooperation, independence, and nationalism complemented by in-depth interviews, participatory observation, and document analysis. Quantitative findings revealed a significant overall increase in students’ Islamic character scores from 68.55 to 81.52 (an improvement of 18.99%), with the integrity dimension recording the highest gain (+22.50%). Pearson correlation analysis confirmed a strong positive relationship between the intensity of Islamic value integration and character improvement (r = 0.742, p < 0.01). Qualitatively, three dominant integration strategies were identified: content-based integration through Islamically themed texts, process-based integration embedding Islamic ethics across all learning stages, and culture-based integration drawing on local Sundanese-Islamic values. These findings demonstrate that Indonesian Language instruction, when intentionally designed as a medium for transmitting Islamic values, functions not only as a linguistic competence builder but also as an effective vehicle for holistic character formation in madrasah students.